Microstructure Abnormalities of Diffusion Tensor Imaging Measures in First‐Episode, Treatment‐Naïve Adolescents With Major Depressive Disorder: An Integrated AFQ and TBSS Study - Wenjie Zhang; Chan Zhang; Jinyuan Zhao; Jiajing Cui; Jinji Bai; Xuan Deng; Junjun Ji; Ting Li; Yu Wang; Kefeng Li; Yunhui Qu; Junfeng Li (Brain and Behavior)
ABSTRACT Purpose Structural changes during depressive episodes in adolescents with major depressive disorder (MDD) remains unclear due to participant heterogeneity, illness chronicity, and medication confounders. This study aimed to explore white matter (WM) microstructural changes in first‐episode, treatment‐naïve adolescents with MDD using an integrated diffusion tensor imaging (DTI) approach. Method We recruited 66 subjects, including 37 adolescents with MDD and 29 healthy controls. Two main DTI techniques, automated fiber quantification (AFQ) and tract‐based spatial statistics (TBSS), were used to analyze fractional anisotropy (FA), axial diffusivity (AD), radial diffusivity (RD), and mean diffusivity (MD) in WM tracts. DTI measures were then correlated with the depressive symptoms evaluated by Hamilton Depression Rating Scale scores (HAMD‐17). Findings In AFQ, MDD patients showed significant segmental differences in WM tracts compared to controls, including a negative correlation between SLF AD values and depression severity. TBSS revealed reduced FA in the cingulum, forceps minor, inferior fronto‐occipital fasciculus, inferior longitudinal fasciculus, SLF, and uncinate fasciculus in MDD. Conclusion Our integrated DTI analysis in a unique first‐episode, medication‐naïve cohort revealed microstructural changes in adolescent MDD not previously reported. These findings may provide imaging markers for early detection and enhance our understanding of depression pathology in youth.